Effects of Alcohol and Psychostimulants on the Vasopressin System: Behavioural Implications - Renard, G (Blackwell Publishing Ltd, 2018)
Drug addiction is a chronic brain disease characterised by a compulsion to seek drugs, a loss of control with respect to drug consumption and negative emotional states, including increased anxiety and irritability during withdrawal. Central vasopressin (AVP) and its receptors are involved in controlling social behaviour, anxiety and reward, all of which are altered by drugs of abuse. Hypothalamic AVP neurones influence the stress response by modulating the hypothalamic-pituitary-adrenal (HPA) axis. The extrahypothalamic AVP system, however, is commonly associated with social recognition, motivational and anxiety responses. The specific relationship between AVP and drugs of abuse has been rarely reviewed. Here, we provide an overview of the interaction between the brain AVP system and psychostimulants and alcohol. We focus on the effects of alcohol and psychostimulants on AVP regulation of the HPA axis, their effect on the brain AVP system and their behavioural implications, the influence of the AVP system on addictive behaviours, and the organisational effects of AVP on the brain and consequently on behaviour. In addition, we highlight clinical studies on the relationship between the AVP system and drug addiction. Finally, we discuss the data aiming to address areas that need further research with respect to supporting clinical trials and preventing drug-related disorders. © 2018 British Society for Neuroendocrinology